Profiles of Housewives with HIV in Surabaya - Hanna Tabita Hasianna Silitonga; Hebert Adrianto; Minarni Wartiningsih; Chindy Claudya Angriyanto (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2021)
Most HIV transmission to housewives was transmission from husbands infected with HIV. The number of housewives infected by HIV was increasing especially in Surabaya. This research aimed to find out the profile of housewives infected with HIV so that strategies can be proposed to prevent transmission to this group. This was a descriptive study with cross-sectional design. The research subjects were housewives with HIV in Surabaya with purposive sampling method. Inclusion criteria were not commercial sex workers (CSWs) or former CSWs, had main role as housewives, one-time marriage history, can read, write, and willing to be respondents. The number of respondents were 58 people. Data was collected by questionnaire containing general characteristics, marital history, husband's history, signs and symptoms of HIV for the first time, history of the first examination, history of disclosure of first time status, and the first source of information about HIV. Data analysis was frequency distribution and percentage. The results showed that the age of majority of respondents were 36-45 years old, high school education, married age 17-25 years, husband's age at marriage 17-25 years, husband's work was an employee, with high school education, history of husband's behavior was having a relationship with other women, the history of the first HIV test was in hospital, with no symptoms, the first source of information about HIV was a doctor, and the majority revealed it to her husband. Proposed strategies in accordance with these profiles are interventions in high school, pre-marriage, marriage, and the husband's workplace setting.